Discoidin domain receptor 1 is a potential target correlated with tumor invasion and immune infiltration in gastric cancer - Wang, Songna; Fu, Yuan; Kuerban, Kudelaidi; Liu, Jiayang; Huang, Xuan; Pan, Danjie; Chen, Huaning; Zhu, Yizhun; Ye, Li (Frontiers in Immunology, 2022)
Discoidin domain receptor 1 (DDR1) has been demonstrated to be able to promote tumor invasion and metastasis, as well as being closely related to tumor immune infiltration. But DDR1 has rarely been studied in gastric cancer. Here, we primarily evaluated DDR1 expression in gastric cancer and its cell lines using Tumor Immunoassay Resource (TIMER), UCSC Xena, Gene Expression Display Server (GEDS) and UALCAN databases. Subsequently, the cancer prognosis was investigated in relation to DDR1 expression using data from The Cancer Genome Atlas (TCGA) database. And DDR1 prognostic value was further analyzed based on clinicopathological characteristics. After analysis, we discovered that DDR1 was highly expressed and significantly connected with poor prognosis in gastric cancer. To comprehensively understand the molecule mechanism of DDR1, we explored genes and proteins interacting with DDR1 in gastric cancer using STRING, PINA and Metascape databases. Additionally, we also examined the effect of DDR1 expression on immune cell infiltration in gastric cancer. The expression level of DDR1 has been found to be inversely correlated with immune infiltration. In order to better understand this mechanism, we studied how DDR1 expression related to gene markers of immune infiltration. Results showed that DDR1 was significantly relative to various immune cell immunolabeling, including FOXP3, CCR8, TGF-β, PD-1, GZMB and so on. Overall, DDR1 was implicated in invasion, metastasis and immune infiltration of gastric cancer. Inhibition of DDR1 may have the potential to alleviate the strong invasiveness and metastasis of advanced gastric cancer. Meanwhile, immune rejection by DDR1 may also provide a new strategy for improving the efficacy of immune checkpoints inhibitors (ICIs), such as programmed cell death protein 1 (PD-1) antibodies.